Design Thinking Research Taking Breakthrough Innovation Home - Plattner, Hasso; Meinel, Christoph; Leifer, Larry (Understanding Innovation, 2016)
In a very unique way, design thinking enables teams and organizations to find completely novel solutions to even complex challenges and to become sustainably innovative. The desire to understand the reason for this effect and to improve our knowledge about innovation drives the HPI Stanford Design Thinking Research Program. Since 2008 scientists from the Hasso Plattner Institute and Stanford University have engaged in multifaceted research projects to find out more about the underlying principles of this method and how and why it works. The outcomes of their studies, experiments, and investigations in the 7th program year have again been compiled and are presented in this book. Special emphasis is placed on exploring how design thinking is applied in practice. This book presents insights from studies and real-world investigations. Research also focuses on design processes with regard to the rising importance of human-technology interaction that comes with technological progress. The third part of this publication compiles findings about prototyping-a core element in design thinking. Finally, design thinking education and training is addressed, presenting promising new approaches and tools. Meaningful insights have been gained by applying rigorous academic methods. And they are not only intended for scientific discourse. Instead they provide guidance and inspiration for all practitioners interested in really comprehending innovation. As we gain a deeper understanding of design innovation processes, the probability of breakthrough innovation increases.